Implementation of the International Classification of Functioning, Disability and Health model in cochlear implant recipients: a multi-center prospective follow-up cohort study - Andries, Ellen; Lorens, Artur; Skarżyński, Piotr Henryk; Skarżyński, Henryk; Calvino, Miryam; Gavilán, Javier; Lassaletta, Luis; Tavora-Vieira, Dayse; Acharya, Aanand; Kurz, Anja; Hagen, Rudolf; Anderson, Ilona; et al. (Frontiers in Audiology and Otology, 2023)
Introduction: No standard protocol based on a multidisciplinary framework currently exists for the evaluation, follow-up and interpretation of Cochlear Implant (CI) outcomes in clinical routine. Therefore, this study aimed to develop and clinically implement a multidimensional Cochlear Implant (CI) outcome assessment protocol for adult CI users based on the International Classification of Functioning, Disability and Health (ICF).Methods: An international multidisciplinary core group of CI experts selected the most relevant ICF categories and codes for adult CI users out of the existing ICF core set for hearing loss. A wellknown, commonly used instrument or method was identified and assigned to each ICF category along with quantified ICF qualifiers. These qualifiers facilitate the interpretation of CI outcomes by categorizing the outcome on a rating scale between 0 and 4, based on the severity of participants' impairment/restriction/limitation/barrier. The ICF-based CI outcome assessment protocol was applied in clinical routine in a prospective longitudinal multicenter study assessing a consecutive sample of 72 adult CI candidates before and six months after implantation. For each relevant ICF category, the participants' improvement, stability or deterioration was specified in a descriptive approach using ICF qualifiers.Results: Participants either showed improved or stable ICF qualifiers after cochlear implantation across all ICF domains (e.g., Body Functions and Structures, Activities and Participation and Environmental factors). The ICF qualifiers for environmental sound tolerance (n = 30 [45%]) and vestibular functions (n = 21 [33%]) deteriorated most frequently after implantation. ICF qualifiers for falling (n = 53 [83%]) and dizziness (n = 40 [62%]) remained stable in most participants. Auditory perception-related and communication-related categories generally improved in most participants after cochlear implantation, with 46% to 73% (n = 34 to n = 48) of CI users perceiving an improvement postoperatively.This study is the first to propose and apply a ready-to-use CI outcome assessment protocol based on the ICF model, which provides a common language and comprehensive assessment protocol for the description and measurement of CI outcomes worldwide. Its straightforward outcome description and rating enables CI outcome interpretation by non-experts, enhancing multidisciplinary communication and knowledge on individual healthcare needs in CI users.